2018
DOI: 10.1002/jor.24155
|View full text |Cite
|
Sign up to set email alerts
|

Topical rifampin powder for orthopaedic trauma part II: Topical rifampin allows for spontaneous bone healing in sterile and contaminated wounds

Abstract: Infectious complications can reduce fracture healing rate. Broad spectrum antibiotics are commonly administered to prevent and treat musculoskeletal infections. Local antibiotics are applied to the wound site to increase therapeutic concentrations without increasing systemic toxicity, however, may hinder local tissue recovery. Rifampin has been shown to eradicate mature Staphylococcal biofilms and its use proven for treating musculoskeletal infections. In this study, a spontaneously healing defect model in a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 45 publications
1
18
0
1
Order By: Relevance
“…The histological studies showed that the edges of both types of sponges were settled by cells that migrated from the surrounding tissues and that the healing process was initiated as soon as after just 5 days (Figures 13 and 14 ). This is also in agreement with previously conducted studies involving bone healing rat models in which neither rifampin nor vancomycin powder added to a bone fracture proved any signs of healing impairment [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…The histological studies showed that the edges of both types of sponges were settled by cells that migrated from the surrounding tissues and that the healing process was initiated as soon as after just 5 days (Figures 13 and 14 ). This is also in agreement with previously conducted studies involving bone healing rat models in which neither rifampin nor vancomycin powder added to a bone fracture proved any signs of healing impairment [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…Other relevant features include: unexpensiveness and easiness of preparation and and handling. It has also been consistently shown to decrease wound infection in other surgical settings 4,7,22 . The present study is the first large scale trial to evaluate its preventive potential.…”
Section: Discussionmentioning
confidence: 93%
“…Vancomycin has minimal eradication effect on this respect. In vitro and in vivo studies have shown that Rifampicin is an effective Staphylococcal biofilm eradicator with no adverse effects on bone healing 7 . Rifampicin's mechanism of action is independent of cellular replication since its target is bacterial protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this is consistent with previous reports. Shiels et al [77] demonstrated that the direct addition of rifampin powder to a contaminated wound led to greater callus formation when compared to untreated wounds, while vancomycin powder elicited no effect. Insignificant bone formation of CaPS containing sitafloxacin also supports studies reporting negative effects of fluoroquinolones on fracture healing [78,79].…”
Section: Discussionmentioning
confidence: 99%